2020
DOI: 10.1093/ehjci/ehaa946.3238
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention in octogenarians – a real-world experience from a large non-surgical centre in the UK

Abstract: Background With an ageing population, the demand for percutaneous coronary intervention (PCI) in the elderly is on the rise. Technical advances, better peri-procedural pharmacology and greater operator experience have led to improved outcomes after PCI. Octogenarians as a group, however, have been underrepresented in randomised clinical trials of coronary revascularisation. Observational studies therefore provide useful insights into the safety and efficacy of PCI in this patient population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2,3 Thus, the number of octogenarians referred to PCI is increasing. 2,4 During the study period, around 9% of patients undergoing PCI were octogenarians. Among them more than 50% underwent CPCI, defined by the presence of at least 1 out of 9 CPCI criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Thus, the number of octogenarians referred to PCI is increasing. 2,4 During the study period, around 9% of patients undergoing PCI were octogenarians. Among them more than 50% underwent CPCI, defined by the presence of at least 1 out of 9 CPCI criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Octogenarians are frequently affected by coronary artery disease (CAD), with more than one‐third having manifest angina symptoms and up to 90% with subclinical coronary atherosclerosis; in addition, CAD represents the leading cause of death in this patient group 2,3 . Referral of octogenarians for percutaneous coronary intervention (PCI) to improve symptoms, quality of life and to reduce myocardial infarction (MI) or unplanned revascularization is becoming progressively more frequent 2,4 . Since octogenarians are more likely than younger patients to have advanced CAD with severely calcified lesions or involving left main or multiple vessels, 2,5–8 they more frequently undergo complex PCI (CPCI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a vast amount of evidence from single-centre experiences 248 , RCTs 237,238 , and observational studies 236 that consistently demonstrated no differences in PCI clinical outcomes between NSCs and SCs in general. Building upon this existing knowledge, our current study expands the understanding of CHiP procedures in NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Results from observational studies 235,236 and randomised control trials (RCT) 237,238 around the safety of PCI in NSCs supported the continuation of the those PCI programs.…”
Section: Introductionmentioning
confidence: 97%